Structural drift of Ukraine’s steppe phytosystems under the influence of climatic changes and prognostic scenarios for the first half of the XXI-st century - Tkachenko, V. S.; Boychenko, S.G. (Reports of the National Academy of Sciences of Ukraine, 2014)
The analysis of the ratios of basic ecobiomorphological components in the phytocenosis of Ukraine's steppes in the second half of the XX-th century and at the beginning of the XXI-st century is carried out. The tendency to a degradation of the xeromorphic component by (30 ± 10)% and the reverse tendency to an increase of the mesomorphic component by (20 ± 10)% are established. On the basis of these tendencies, the following prognostic estimations of possible changes in the ratios of the ecobiomorphological components in the phytocenosis are given for the first half of the XXI-st century: a decrease of the xeromorphic component by one third in the southern regions and its almost complete disappearance in the northern regions, as well as the extension of the areas occupied by the mesomorphic and lignostic components.